ENGLISH NEEDS ANALYSIS FOR STUDENTS OF POLYTECHNIC RADIO DIAGNOSTIC ENGINEERING AND RADIOTHERAPY - Masdianti, Masdianti; Nana Erna; Titin Suhartini; Asdar (Journal of English Education and Linguistics, 2024)
This study aims to identify and analyze the need for English for Specific Purposes (ESP) learning materials for students in the Department of Radio Diagnostic Engineering and Radiotherapy (ATRO) at Muhammadiyah Makassar. A needs analysis was conducted to ensure students receive materials that support their learning and career development, using a qualitative approach and descriptive strategy. The research subjects were second-semester students in class B21 and their experienced ESP lecturer, selected through purposive random sampling. Data collection involved observation, recording, questionnaires, and interviews. Key findings from the questionnaire included: 83.3% satisfaction with current ESP materials, 77.8% of students needing English related to Radiology, 55.6% with intermediate English proficiency, and 66.7% aiming to improve their English for professional purposes. Skills priorities were speaking (66.7%), listening (61.1%), reading (33.3%), and writing (33.3%). Effective speaking skills instruction is achieved by dividing the large class into three groups. These findings suggest ESP lecturers and stakeholders should develop lesson plans and teaching media aligned with these needs. Additionally, the ESP lecturer identified Merrill's Atlas of Radiographic Positions and Radiological Procedures as a key resource for material development.